Motherhood should not be this hard : women seek relational care from their perinatal health providers : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Albany, New Zealand - Feder, Kate (Massey University, 2025)
Mothering practices and underlying understandings of motherhood can vary with cultural, class, societal, and temporal contexts. In Aotearoa New Zealand, the Western-dominant construction of motherhood, known as intensive mothering, is child-centred and places the responsibility of child-rearing primarily on mothers. Poor mental health outcomes for mothers, and mental health inequities between mothers and non-mothers are rising; in Aotearoa New Zealand, this effects between 12 to 19 percent of mothers; likely higher for Māori women. The purpose of this study was to explore four cases to exemplify how new mothers navigate motherhood. With particular focus on how the dominant constructions of neoliberalism and managerialism, motherhood, disease and repair, and health and illness, transmitted through public organisations, influenced their identities and experiences. I further investigated whether the Aotearoa New Zealand health system is serving economically privileged, Pākehā women who have historically had more positive health outcomes than Māori women. This research was conducted using case-based narrative inquiry enacted through semi-structured interviews and participatory mapping to support the participating mothers to express their experiences in the contemporary health system. Findings suggest that not only is the health system not serving Pākehā mothers but also features what participants described is a Kafkaesque bureaucracy which obstructs the provision of quality healthcare and may have negatively contributed to their mental health during the perinatal period. Participants rejected the service providers which fell short of their expectations and instead opting for clinicians with whom they had a connection, and providers grounded in relational values. These findings have implications for how motherhood is understood in Aotearoa New Zealand and offer insights that support the need for implementing more person-centred healthcare support for mothers.
Keywords: 520304 Health psychology